Genome scan for parent-of-origin QTL effects on bovine growth and carcass traits - Ikhide G. Imumorin (Frontiers in Genetics, 2011)
Parent-of-origin effects (POE) such as genomic imprinting influence growth and body composition in livestock, rodents and humans. Here, we report the results of a genome scan to detect quantitative trait loci (QTL) with POE on growth and carcass traits in Angus x Brahman cattle crossbreds. We identified 24 POE-QTL on 15 Bos taurus autosomes (BTAs) of which 6 were significant at 5% genome-wide level and 18 at the 5% chromosome-wide significance level. Six QTL were paternally expressed while 15 were maternally expressed. Three QTL influencing post-weaning growth map to the proximal end of BTA2 [linkage region of 0 – 9 cM; genomic region of 5.0 – 10.8 Mb], for which only one imprinted orthologue is known so far in the human and mouse genomes, and therefore may potentially represent a novel imprinted region. The detected QTL individually explained 1.4% ~ 5.1% of each trait’s phenotypic variance. Comparative in-silico analysis of bovine genomic locations show that 32 out of 1,442 known mammalian imprinted genes from human and mouse homologues map to the identified QTL regions. Although several of the 32 genes have been associated with quantitative traits in cattle, only 2 (GNAS and PEG3) have experimental proof of being imprinted in cattle. These results lend additional support to recent reports that POE on quantitative traits in mammals may be more common than previously thought, and strengthen the need to identify and experimentally validate cattle orthologues of imprinted genes so as to investigate their effects on quantitative traits.